Social aid in online news : tracking the issues of resilient society - Hastjarjo, Sri; Rutiana Dwi Wahyunengseh, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Indonesia’s Ministry of Finance stated that in a two-month period, the number of poor people grew by 1.1 to 3.78 million as an impact of Covid‐19 pandemic, which is a threat to the resilient society in Indonesia. To deal with the problem, the Government issued Bantuan Sosial Covid‐19 (Bansos Covid‐19), a social aid programme for the population impacted by the pandemic. The implementation of Bansos Covid-19 and its effects are reported and discussed in several online news media in Indonesia. This study aims to present the issues of Bansos Covid-19 implementation as reported by the online news media from the perspective of the concept of resilient society suggested by Patel, Rogets, Amlot, and Rumin (2017). Using a content analysis method, this study analysed news items containing keywords Bantuan Sosial Covid‐19 published between 1 April and 30 June 2020. Textual data analysis was conducted by using the N‐Vivo program, software dna.20 ‐ beta2.5, and visualisation of results with visone 2.18. This study found that there are some issues arising from the implementation of Bansos Covid‐19, including the problems of data validity, the overlapping regulations, the distribution management, and the disposition of the program implementer. This study also identifies some positive effects including the support of the business sector and various community groups. This study concludes that the Bansos Covid‐19 policy has potential to impact the elements of a resilient society.